Rancang Bangun Aplikasi Pendaftaran Program Internasional Menggunakan Metode User Centered Design - Muthi Amrillah; Rahmalia Syahputri; Sherli Trisnawati; Taufik Taufik (SMATIKA JURNAL : STIKI Informatika Jurnal, 2025)
This study focuses on designing and developing an international program registration application using the User-Centered Design (UCD) approach. The UCD method is implemented to create an optimized user interface and experience, prioritizing the needs of both local and international students. The application replaces the previously used Google Form-based system, which had limitations in data security, database management, and selection process integration. The development process follows UCD principles, including context of use identification, user and organizational needs analysis, high-fidelity prototype design, and evaluation using the System Usability Scale (SUS). The initial evaluation resulted in an SUS score of 65 (Marginal High), which improved to 72 (Acceptable) after a redesign. The application is developed using Dart for the frontend and Firebase for the backend, ensuring flexibility in feature expansion. This solution enhances registration efficiency, improves the user experience, and supports multilingual and cross-device accessibility. Ultimately, this research contributes to technological innovation in international program management while strengthening the institution’s competitiveness in global higher education.